The Morphofunctional Response of T-Lymphocytes to in vitro Contact with a Calcium Phosphate Coating in the Presence of a T-Cell Activator; Cell and Tissue Biology; Vol. 15, iss. 1 - Litvinova L. S. Larisa Sergeevna; Melashchenko E. S. Elena Sergeevna; Khaziakhmatova O. G. Olga Gennadjevna; Yurova K. A. Kristina Alekseevna; Sharkeev Yu. P. Yury Petrovich; Komarova E. G. Ekaterina Gennadjevna; Sedelnikova M. B. Mariya Borisovna; Todosenko N. M. Nataljya Mikhaylovna; Khlusov I. A. Igor Albertovich (2021, 2021)
Title screen